Philippine banking almanac - Litiatco, Vicki J. (DRTI Consultancy (Phils), Inc., 1993)
A listing of Philippine banking institutions to aid businessmen and financial executives in the country. Includes selected articles by stalwarts in the banking community, primers on money market and trust operations. The almanac's highlight is its detailed listing of government and private banks in the country.